2019
DOI: 10.4183/aeb.2019.466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Hypothalamic-Pituitary-Adrenal Axis in a Paediatric Intensive Care Unit

Abstract: Background. Relative adrenal insufficiency (RAI) is the inadequate production of cortisol due to dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis during a severe illness. We evaluated the HPA axis and RAI in a tertiary pediatric intensive care unit (PICU).Methods. A total of 100 PICU patients were included in this prospective cohort study. Basal serum levels of adrenocorticotropic hormone (ACTH), cortisol values were compared with those in the control group. A low-dose ACTH stimulation test was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A total of 21 observational studies published before 2022 were analyzed, with a total of 2,212 enrolled subjects, of whom 57.97% were male and 42.03% were female. 5,6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The sample consisted of 1,810 subjects with critical illness, including 916 subjects with sepsis and septic shock, and 402 control subjects. The characteristics and outcomes of included studies are shown in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 21 observational studies published before 2022 were analyzed, with a total of 2,212 enrolled subjects, of whom 57.97% were male and 42.03% were female. 5,6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The sample consisted of 1,810 subjects with critical illness, including 916 subjects with sepsis and septic shock, and 402 control subjects. The characteristics and outcomes of included studies are shown in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen of 21 studies stated that there was a relationship between elevated cortisol levels and mortality in critical illness patients, including those with sepsis, as shown in Table 3. 5,6,[13][14][15][16][17][19][20][21][22][24][25][26][27][28][29][30] One study agreed with the statement, but found no relationship between postserum ACTH stimulation test and mortality in critical illness patients. 17 Fourteen studies had mortality percentage data critical illness patients with elevated cortisol levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that the presence of adrenal failure in patients with a septic state (including both sepsis and septic shock) is associated with increased mortality and a long duration of intensive care unit stay. It also seems that the need for inotropic support and high doses of inotropic drugs might be considered as an indicator of adrenal insufficiency in ICU patients [ 8 ].…”
Section: Managementmentioning
confidence: 99%